Tech Recruiting Foundations: 5 Waterfall, Agile, and DevOps for Recruiters. - Shaikh, Ayub; Consulting, Holistica (linkedin.com, 2021)
Learn enough about tech to be able to recruit and hire effectively for different roles in IT.